(untitled) (Applied Biological Research, 2017)
The present study focused on the classification and identification of bioactive components, along with functional groups, present in methanolic seed-extract of fenugreek (Trigonella foenum-grecum L.) var. Gujarat Methi-2 (GM-2). Seed were analyzed using GC-MS-QP2010 Ultra and FT-IR by alpha ECO ATR spectrometer. The mass spectra of compounds matched with National Institute of Standards and Technology (NIST) library. GC/MS analysis of methanol extract of var. GM-2 seed revealed the presence of 50 bioactive compounds amongst which 9, 12-octadecadienoic acid (Z, Z)- (32%), mome inositol (12%), cyclopentanol (9%) and 2-methylpyrrolidine (3%) were most dominant. Peaks obtained from FT-IR indicated the presence of various functional groups. The results offer a platform for using var. GM-2 seed as herbal alternative for synthetic antimicrobial and antioxidants sources.